2021
DOI: 10.1016/j.clnu.2021.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns acquired in early life are associated with cardiometabolic markers at school age

Abstract: Background & aims: it has previously been described that dietary patterns established early in life tracked to late childhood. The aim of the present work was to analyse the association of dietary patterns that tracked from 2 to 8y with cardiometabolic markers at 8y of age. Methods: The 3 identified patterns at 2y (that previous analyses showed to track to age 8y) were: "Core DP ", loaded for vegetables, fruits, fish, olive oil, etc.; "F&S DP ", loaded by poor-quality fats and sugars; and "Protein DP ", mainly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Our results should be interpreted within the context of adequate protein intake, and cardiometabolic profiles frequently characterised by low HDL-c, but very little overweight or obesity (27) . While inadequate protein growth can lead to poor growth outcomes, high protein intake, especially MFP protein, is associated with increased weight gain during infancy and correlates with later obesity (1) , but decreased risk of cardiometabolic disease for individuals who were stunted as children (21) . Protein intake is also highly related to overall dietary quality (23) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results should be interpreted within the context of adequate protein intake, and cardiometabolic profiles frequently characterised by low HDL-c, but very little overweight or obesity (27) . While inadequate protein growth can lead to poor growth outcomes, high protein intake, especially MFP protein, is associated with increased weight gain during infancy and correlates with later obesity (1) , but decreased risk of cardiometabolic disease for individuals who were stunted as children (21) . Protein intake is also highly related to overall dietary quality (23) .…”
Section: Discussionmentioning
confidence: 99%
“…These findings are supported by studies from HICs which have found that protein intake, and the ratio of animal to plant protein, are negatively associated with diverse components of cardiometabolic health (22,23) . In HICs, positive, negative and null associations have been reported between protein intake in infancy and cardiometabolic risk factors such as blood pressure, triglycerides and serum insulin (1,24,25) . This lack of consistency may derive from the fact that the relationship between specific nutrients and cardiometabolic risk is complex, and nutrients are often consumed in relation to other aspects of diet, which may be risk-promoting or protective.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It seems that eating habits acquired in the first 2 years of life are unchanged at 8 years of age. Thus, the adoption of healthy eating habits in preschool and school-aged children should be promoted as early as possible [32].…”
Section: Key Factors After Two Years Of Life Related To Obesity Riskmentioning
confidence: 99%
“…Dietary patterns established in early childhood can persist into adulthood ( 9 , 12 ). The pattern and quality of diet in childhood are longitudinally associated with weight and cardiometabolic markers ( 13 , 14 ). Therefore, early childhood is a critical period for dietary education and development of eating habits ( 15 ).…”
Section: Introductionmentioning
confidence: 99%